The last occurrence of Megaceroides algericus Lyddekker, 1890 (Mammalia, Cervidae) during the middle Holocene in the cave of Bizmoune (Morocco, Essaouira region). (10th July 2015) - Fernandez, Philippe; Bouzouggar, Abdeljalil; Collina-Girard, Jacques; Coulon, Mathieu
Abstract: During the course of archaeological test excavations carried out in 2007 in the cave of Bizmoune (Essaouira region, Morocco), seven archaeological layers yielding Pleistocene and Holocene artefacts and faunal remains were identified. In the layers C4, C3 and C2, respectively from the oldest to the most recent, terrestrial Helicidae mollusk shells ( Helix aspersa ) were dated by 14 C. These layers also contained many fragments of eggshell, belonging to Struthio cf. camelus, associated with mammal remains such as Oryctolagus/Lepus, Gazella sp., Sus scrofa, Ammotragus lervia, Alcelaphus buselaphus, Equus sp., Phacochoerus aethiopicus and an undetermined Caprini. Among these remains, an incomplete mandible of Megaceroides algericus Lydekker, 1890 with M1 and M2 was found in layer C3. The 6641 to 6009 cal BP time range attributed to this layer has provided the most recent date known so far for M. algericus. In this study, we review and contextualize the findings of this particular species both in time and space and discuss its systematic position. We describe the morphology of the typical pachyostosic mandibular bone with the teeth and compare the dimensions with existing data. The assumption of the combined development, on the one hand, of the pachyostosic phenomenon and on the other hand, of the body weight fluctuations and growth of antlers for cervids strongly affected by seasonality is not supported. In order to understand the origin and the extinction of M. algericus, we examined the AMS radiocarbon dates available in the literature and calibrated them with RenDateModel software. Comparisons are then made with sea surface temperatures ( e.g. GISP2 δ 18 O), eustasy and related environmental changes throughout the time span of this species. Based on these data a possible migration route by the Strait of Gibraltar connected with with eustatic rises in sea-level rises are discussed. The speciation-extinction processes for M. algericus and their correlations with climatic shifts on a long time-scale in North Africa ( e.g. Heinrich events, 8200 cal BP event) are also considered. Finally, this new discovery in Bizmoune cave clearly shows that M. algericus lasted until the very end of the Epipaleolithic, around 6000 cal BP (middle Holocene), whereas this species was formerly not believed to have survived until the early Epipaleolithic (around 8000 cal BP).